2001
DOI: 10.1002/j.2048-7940.2001.tb02211.x
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Care During the Stroke Experience

Abstract: This article describes a model we developed to guide the selection and design of nursing activities that will facilitate the health of persons with stroke and their families. Care in the context of stroke has been structured by the medical model's focus on functional ability. As a result, nursing is viewed as ancillary to other professions; yet, studies of the stroke experience from the patient's view suggest that distinctive nursing interventions are needed. Current models of illness do not sufficiently addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Treatment burden has not been well examined in relation to stroke. Previous syntheses of qualitative studies in stroke have focussed either on the patient experience of illness rather than treatments [26],[27],[28] or on the experience of informal carers [29],[30]. A few syntheses have explored the patient experience of stroke treatments, but these have concentrated either on one specific aspect of the management process [31][38] or specifically on the interaction between patient and health care providers [39][41].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment burden has not been well examined in relation to stroke. Previous syntheses of qualitative studies in stroke have focussed either on the patient experience of illness rather than treatments [26],[27],[28] or on the experience of informal carers [29],[30]. A few syntheses have explored the patient experience of stroke treatments, but these have concentrated either on one specific aspect of the management process [31][38] or specifically on the interaction between patient and health care providers [39][41].…”
Section: Introductionmentioning
confidence: 99%
“…2000, p. 511). Indeed, it has been suggested that stroke has a far greater impact on an individual than other diseases because brain function is at the very essence of what we regard as ‘humanness’ (Brauer et al. 2001, p. 90).…”
Section: Introductionmentioning
confidence: 99%
“…But, stroke patients' experience of life after the event is characterized by existential aspects of suffering and loss (Pilkington, 1999;Secrest & Thomas, 1999). Stroke is considered to be a lifetransforming event by those it affects (Brauer, Schmidt, & Pearson, 2001). Much has been reported on patients' post-discharge limitations in physical (de Wit et al, 2007), cognitive (Wagle et al, 2011), and emotional functioning (Bergersen, Frey Froslie, Stibrant Sunnerhagen, & Schanke, 2010;Herrmann, Black, Lawrence, Szekely, & Szalai, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the fact that patients may have regained a certain level of functioning, most patients cannot return home without informal care and the support of a social network (Meijer et al, 2004). The immediate post-discharge period is described as difficult, demanding and stressful , and greatly marked by uncertainty (Brauer, et al, 2001;Carlsson, Möller, & Blomstrand, 2009). It is probably only at home that patients and their families will fully understand the consequences imposed by stroke (Olofsson, Andersson, & Carlberg, 2005).…”
Section: Introductionmentioning
confidence: 99%